Ejercicio físico para mujeres postmenopáusicas. - Mera Espinoza, Dailyn Lilibeth (2025)
Introduction: Menopause is considered the end of a woman's reproductive life. One year after the cessation of the menstrual cycle, the postmenopausal stage begins. During this phase, hormonal imbalances in the body can lead to various pathologies affecting the cardiovascular, metabolic, skeletal, and muscular systems. Physical exercise during this stage may serve as a highly effective therapeutic alternative for improving the overall health of postmenopausal women. Objective: To synthesize the scientific evidence on the effects of physical exercise in postmenopausal women and its reported outcomes, in order to provide a solid foundation for future research and its implementation in clinical practice. Methodology: The study is of a bibliographic type, randomized clinical trials were collected from scientific databases such as PubMed and PEDro with the proposed subject matter and inclusion and exclusion criteria were used for their selection. Results: a total of 30 scientific trials were added for the development of the research, which were evaluated by the PEDro scale to determine their validity. Conclusions: Physical exercise has proven to be an effective intervention for improving the overall health of postmenopausal women. Through the application of structured and targeted exercise programs, it is possible to address specific health needs. For instance, at the skeletal level, an active lifestyle stimulates osteoblastic activity, leading to increased bone mineral density. Similarly, at the muscular level, exercise promotes gains in lean muscle mass and reductions in body fat, both of which contribute to improved cardiometabolic health.